Mewujudkan Good Local Goverance Melalui Transparansi Dan Akuntabilitas Anggaran Publik - Rofikoh, Nurul (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2006)
Secret bureaucracy culture to public budget have created itsfed& OI of corruption growth in various area, so that can menace its form of good local governance . Therefore transparency represent one of the elementary aspect which require to conduct to its form of management arrange good governance. With society transparency as stakeholders earn precise, critic*, or even evaluate as forming of public participation which become important comitionfor the creation of governance good.